2016
DOI: 10.4103/2229-516x.192587
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid disorders in hepatitis C virus positive patients on interferon and antiviral therapy

Abstract: Background:Hepatitis C virus (HCV) infection is common worldwide. The treatment typically involves a combination of interferon-alpha (IFN-α) and ribavirin (RBV) therapy; however, the use of IFN-α is well documented to be associated with thyroid disease, the most common autoimmune disorder associated with IFN-α.Aim:The aim of the present study was to know the prevalence of thyroid abnormality in the HCV-positive patients on IFN and antiviral therapy.Materials and Methods:Fifty known HCV positive patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…In a similar study, Goyal et al (2016) [7]. It can be said that results of previous studies are comparable with results of this study as well.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a similar study, Goyal et al (2016) [7]. It can be said that results of previous studies are comparable with results of this study as well.…”
Section: Discussionsupporting
confidence: 89%
“…There is no or weak association between severity of the disease and response to therapy with IFN-induced thyroid dysfunction. 13 (26%) of the patients were found to develop hypothyroidism, and 1 (2%) patient developed hyperthyroidism in the course of 12 weeks therapy [13]. It was observed that female patients (10.4%) had relatively higher rate of developing hypothyroidism than male patients.…”
Section: Discussionmentioning
confidence: 95%
“…One study revealed that overt AITD occurred in about 5–10% of INF- α -treated patients [24]. A recent study has also found that 2% of patients developed hyperthyroidism in the HCV-positive patients during a 12-week course of INF- α antiviral therapy [25]. Therefore, studies have indicated that INF- α is one of the important immune factors that induce AITDs [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…2 Existing literature suggest that thyroid dysfunction is the most common endocrine disorder that occurs in HCV infected patients and interferon (IFN) therapy has been associated with an increase in thyroid disorders. [3][4][5][6] This is the first-ever evidence to report thyroid dysfunction in two different groups of chronic hepatitis C (CHC) patients treated with two different direct-acting antiviral (DAA) drug combinations that are sofosbuvir + ribavirin + pegylated-IFN-α and sofosbuvir + ribavirin + daclatasvir.…”
Section: Introductionmentioning
confidence: 99%